An update on phytoconstituents and pharmacological importance of Asparagus racemosus - Meher, Deepak; Singh , Mithlesh; Meher , Bibekananda (Journal of Applied Pharmaceutical Research, 2024)
Background: Asparagus racemosus (family: Liliaceae), is a well-researched traditional or ancient medicine in the Siddha, Ayurveda, and Unani systems. It is commonly known as Satawar, Satamuli, Satavari, and found at low altitudes throughout India. It contains bioactive metabolites such as fructo-oligosaccharides, polysaccharides, asparosides, shatavarins, sapogenins, racemosols, isoflavones, glycosides, mucilage, and fatty acids, while saponin is one of the main active constituents of asparagus. Objective: Across the globe, Asparagus racemosus gained importance for its ethano-pharmacological value in curing various ailments. This review will outline the medicinal properties, uses, and value addition of Asparagus racemosus. Methods: We have reviewed and retrieved the relevant information by probing the main keywords in online databases (PubMed, Scopus, Science Direct and Web of Science, etc.). Screening of relevant abstracts/ title and full papers were done to pick the suitable content based on the pharmacological profile of Asparagus racemosus. Conclusion: The whole plant possesses pleiotropic therapeutic activity, antioxidant, anti-inflammatory, immunomodulatory, neuroprotective, nootropic, antidepressant, etc., without showing any remarkable side effects. It also treats stomach ulcers, diabetes, kidney disorders, and Alzheimer's disease, etc.